Zonation and distribution of crabs in Pichavaram mangrove swamp, southeast coast of India - Ravichandran, S; Soundarapandian, S; Kannupandi, T (Indian Journal of Fisheries, 2011)
The zonation and distribution of crabs were studied in Pichavaram mangroveswamp. The season-wise distribution of crab species was maximum among themanagal trees, especially Rhizophora and Avicennia species and open mud flatswith mixed forests. Twenty three species of crabs were recorded from the mangrove.The species richness of crabs was higher in creek mangrove vegetation thanin fringe mangrove types. Comparisons showed that the species composition ofthe crabs in the Sesarma zone was widely varied when compared to otherCardisoma, Ocypoda, Uca in mixed zones. More population and high species compositionwere recorded in the postmonsoon period. Each zone exhibited in characteristicspecies diversity. Distribution and zonation of crabs were based on thesubstratum, water level and floral distribution.